Decade Long Study on Colonial Nesting of Waterbirds in Bhitarkanika National Park, Odisha, India - Pradhan, Soumya Darshan; Kar, Sudhakar (Indian Forester, 2018)
The objective of decade long study on colonial nesting of waterbirds in heronries of Bhitarkanika National Park was to enumerate species wise nest number, choice of nesting trees, documentation of the vegetation characteristics, population trends etc. Nesting of waterbirds in two heronries such as Bagagahan and Matha-Adia has been studied and analysed. A total of ten waterbird species i.e. Asian openbill stork (Anastomus oscitans), Little cormorant (Phalacrocorax niger), Little egret (Egretta garzetta), Intermediate egret (Egretta intermedia), Large egret (Ardea alba), Purple heron (Ardea purpurea), Night heron (Nycticorax nycticorax), Grey heron (Ardea cinerea), Oriental darter (Anhinga melanogaster), Black headed ibis (Threskiornis melanocephalus) were recorded to be nesting together in the heronries of Bhitarkanika. Asian openbill stork was the dominant species in both the heronries. In the last one decade, maximum 21204 nests were reported in the year 2016 and minimum 7206 nests in the year 2010. In 2012, Bagagahan heronry split apart and a new heronry at Matha-Adia came into existence. Asian openbill stork comprised nearly 76 % of nesting waterbirds population in both the heronries. Little egret and Black headed ibis had the least number of nests in the heronries comprised of only one percent of nesting waterbird population.